Personalised Fitness Program using K-means Clustering - Devi Rajagopal, Renuka; Gurumurthy, Sasikumar; Chachuliya, Hatim; Deka, Mriganav (International Journal of Engineering and Technology, 2018)
As the adoption rate ofÂ Â smart phoneâ€™s and tablets have skyrocketed, it has become easier for people to access information on these devices. This software program aims to help keep track and pursue the fitness goals of the person using it by specifically making diet and workout plans for him/her according to his/her body type.